2018
DOI: 10.1016/j.molcel.2017.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Interactome Screening Identifies the ER Luminal Chaperone Hsp47 as a Regulator of the Unfolded Protein Response Transducer IRE1α

Abstract: Maintenance of endoplasmic reticulum (ER) proteostasis is controlled by a dynamic signaling network known as the unfolded protein response (UPR). IRE1α is a major UPR transducer, determining cell fate under ER stress. We used an interactome screening to unveil several regulators of the UPR, highlighting the ER chaperone Hsp47 as the major hit. Cellular and biochemical analysis indicated that Hsp47 instigates IRE1α signaling through a physical interaction. Hsp47 directly binds to the ER luminal domain of IRE1α … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
158
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(160 citation statements)
references
References 76 publications
1
158
0
1
Order By: Relevance
“…Further cell-based and structural studies are needed to define the IRE1β–IRE1α interaction and how distinct IRE1β/IRE1α assemblies confer preference for XBP1 cleavage versus RIDD activity. Likewise, other ER proteins (Amin-Wetzel et al, 2017; Bertolotti et al, 2000; Sepulveda et al, 2018; Sundaram et al, 2017) and mediators of apoptosis (Lisbona et al, 2009; Shemorry et al, 2019) also regulate IRE1α activity. How IRE1β affects these interactions and regulatory mechanisms also remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Further cell-based and structural studies are needed to define the IRE1β–IRE1α interaction and how distinct IRE1β/IRE1α assemblies confer preference for XBP1 cleavage versus RIDD activity. Likewise, other ER proteins (Amin-Wetzel et al, 2017; Bertolotti et al, 2000; Sepulveda et al, 2018; Sundaram et al, 2017) and mediators of apoptosis (Lisbona et al, 2009; Shemorry et al, 2019) also regulate IRE1α activity. How IRE1β affects these interactions and regulatory mechanisms also remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…A FRET UPR induction assay, developed to quantify the association and dissociation of the IRE1 luminal domain from BiP upon ER stress , demonstrated that the ER luminal co‐chaperone ERdj4/DNAJB9 represses IRE1 by promoting a complex between BiP and the luminal stress‐sensing domain of IRE1α . Moreover, it has recently been reported that another ER luminal chaperone, Hsp47, displaces BiP from the IRE1 UPRosome to promote its oligomerization . Once released from BiP, IRE1 and PERK homodimerize or oligomerize and trans‐autophosphorylate to activate their downstream pathways .…”
Section: Er Stress Consequencesmentioning
confidence: 99%
“…Under these conditions, the transmembrane domain and the cytosolic effector domains ‘follow’ the oligomerization of the ER-luminal domains. A large diversity of ER-luminal and cytosolic interactors including chaperones can tune and specify the activity of mammalian UPR transducers (14, 48). This may reflect a way to custom-tailor the globally-acting UPR to different cell types with distinct protein folding requirements during steady-state and particularly during differentiation.…”
Section: Discussionmentioning
confidence: 99%